Effect of inspiratory muscle warm-up on submaximal rowing performance - Arend, M.; Mäestu, J.; Kivastik, J.; Rämson, R.; Jürimäe, J. (The Journal of Strength and Conditioning Research, 2015)
Performing inspiratory muscle warm-up might increase exercise performance. The aim of this study was to investigate the impact of inspiratory muscle warm-up to submaximal rowing performance and to find if there is an effect on lactic acid accumulation and breathing parameters. Ten competitive male rowers aged between 19 and 27 years (age, 23.1 ± 3.8 years; height, 188.1 ± 6.3 cm; body mass, 85.6 ± 6.6 kg) were tested 3 times. During the first visit, maximal inspiratory pressure (MIP) assessment and the incremental rowing test were performed to measure maximal oxygen consumption and maximal aerobic power (Pamax). A submaximal intensity (90% Pamax) rowing test was performed twice with the standard rowing warm-up as test 1 and with the standard rowing warm-up and specific inspiratory muscle warm-up as test 2. During the 2 experimental tests, distance, duration, heart rate, breathing frequency, ventilation, peak oxygen consumption, and blood lactate concentration were measured. The only value that showed a significant difference between the test 1 and test 2 was breathing frequency (52.2 ± 6.8 vs. 53.1 ± 6.8, respectively). Heart rate and ventilation showed a tendency to decrease and increase, respectively, after the inspiratory muscle warm-up (p < 0.1). Despite some changes in respiratory parameters, the use of 40% MIP intensity warm-up is not suggested if the mean intensity of the competition is at submaximal level (at approximately 90% maximal oxygen consumption). In conclusion, the warm-up protocol of the respiratory muscles used in this study does not have a significant influence on submaximal endurance performance in highly trained male rowers.